Clean intermittent catheterisation determinants and caregiver adherence in paediatric patients with spinal dysraphism and spinal cord injury in a paediatric spinal differences clinic: a mixed methods study protocol - Azadeh Wickham; Cynthia L Russell; John M Gatti (BMJ Open)
Introduction Clean intermittent catheterisation (CIC) is the standard of care for treating neurogenic lower urinary tract dysfunction (NLUTD), the most common bladder dysfunction in children diagnosed with spinal dysraphism (SD) and spinal cord injury (SCI). Failure to follow the prescribed CIC regimen results in urinary tract infections, incontinence and renal insufficiency. Adherence to CIC is suboptimal, with reported non-adherence rates of 18%–66%. Despite the efficacy of CIC, the research on CIC adherence is not well defined in the literature and even less for caregivers of children on CIC protocols.Methods This proposed study aims to identify caregiver CIC adherence and determinants while exploring the personal experiences of performing CIC from the perspective of caregivers of children with NLUTD due to SD and SCI. This cross-sectional, correlational, convergent mixed methods study design in which qualitative and quantitative data will be collected simultaneously will be used to study the level of adherence and the relationship of caregiver determinants to CIC in children with SD and SCI and adherence to the CIC protocol. Convenience sampling will be used to identify 60 adult caregivers who can read and write English or Spanish and have a child diagnosed with SD and SCI who is currently prescribed CIC by a urology provider.Analysis The adherence data will be reported as frequency and percentages. A correlation analysis will be computed to assess the association between determinants measured by the Clean Intermittent Catheterization-Caregiver Questionnaire and adherence levels measured with the Intermittent Catheterization Adherence Scale. Thematic analysis will be used to analyse and interpret the interview data. A comparison joint display will be developed to compare quantitative and qualitative data results.Ethical and dissemination Institutional review board approval was obtained from the Children’s Mercy Kansas City (Study00003003) and the University of Missouri-Kansas City (#2100185). The study’s main results will be disseminated to caregiver participants, published in peer-reviewed journals and presented at conferences.